Potensi Situs Masjid Makam Mantingan dan Makam Auliya Daeng Sebagai Sumber Belajar Sejarah Kebudayaan Islam Indonesia - Asyif Awaludin Romadhoni; Raden Roro Anisa Khaura; Aman Aman; Muhammad Ertam Hidayat (Jurnal Keislaman, 2023)
The research aims to determine the history of Islamic heritage in Jepara, namely the Mantingan Mosque and Tomb site and the Auliya Daeng Tomb. Qualitative methods are used with historical approaches including heuristics, source verification, data interpretation and report writing. The Mantingan Mosque is a cross-cultural blend in Jepara society. The shape of the mosque which is tall and has steps in common with the punden terraces, a relic of the pre-literate era, namely the Megalithic era. On the roof of the mosque you can see the shape of a joglo like a traditional Javanese house, but at the end of the roof there is a pointed shape like a Chinese ethnic house. On the walls of the mosque there are also white stone carvings as the influence of Hindu-Buddhist and Chinese culture. This description explains that the Mantingan Mosque is a concrete example of a harmonious blend of cultures by the people of Jepara during the early days of the spread of Islam in Indonesia. Auliya Daeng Tomb is a historical site located not far from the Mantingan Mosque and Tomb. Auliya Daeng's grave site is located in Krapyak Village, Tahunan District, Jepara. The tomb has something in common with the presence of ancient brick construction in the tomb. Other forms of gravestones have Bugis, Aceh and Demak influences. This legacy indicates that Islam in Java developed long before Demak was founded. In addition, the discovery of Auliya Daeng's grave is a form of tolerance for the Indonesian people, who have always been diverse and multicultural.